2017
DOI: 10.1056/nejmc1709849
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Mortality in the Medicare Population

Abstract: Background-Studies have shown that long-term exposure to air pollution increases mortality. However, evidence is limited for air-pollution levels below the most recent National Ambient Air Quality Standards. Previous studies involved predominantly urban populations and did not have the statistical power to estimate the health effects in underrepresented groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…[1][2][3] In this assessment, the prevalence was 19.9% in boys and 23.6% in girls between the ages of 5 and 17 years in 2015. 4 These estimates are much higher than the GBD estimates of 10.6% in boys and 15.1% in girls between the ages of 2 and 19 years in 2015. The authors of the GBD study acknowledge a number of limitations they faced in deriving their estimates, including missing or heterogeneous data in many countries, factors that underlie their use of complex statistical models.…”
Section: Doi: 101056/nejmc1710026mentioning
confidence: 80%
See 3 more Smart Citations
“…[1][2][3] In this assessment, the prevalence was 19.9% in boys and 23.6% in girls between the ages of 5 and 17 years in 2015. 4 These estimates are much higher than the GBD estimates of 10.6% in boys and 15.1% in girls between the ages of 2 and 19 years in 2015. The authors of the GBD study acknowledge a number of limitations they faced in deriving their estimates, including missing or heterogeneous data in many countries, factors that underlie their use of complex statistical models.…”
Section: Doi: 101056/nejmc1710026mentioning
confidence: 80%
“…[1][2][3] Approximately half of all adults with excess body fat are defined as nonobese on the basis of BMI, 1 and bias is even greater in some populations (e.g., East Asians and South Asians). 4 The GBD study used the most conservative of the available options to define obesity in children and adolescents. 2 BMI is a practical measure and is highly specific for excess fatness, 1-3 but its inherently low sensitivity should be more widely appreciated and should be noted when estimates of obesity prevalence are provided.…”
Section: Doi: 101056/nejmc1710026mentioning
confidence: 99%
See 2 more Smart Citations
“…Over a decade ago, dermatologist Jean Krutmann began postulating how pollutants in the environment affect the skin. Evidence has shown that airborne pollutants harm the skin, and may even be deadly [ 13 , 25 , 26 ]. A recent epidemiological study has reported that indoor and outdoor air pollution also increase the risk of asthma, wheezing, rhinitis and eczema among pre-school children in China [ 27 ].…”
Section: Discussionmentioning
confidence: 99%